(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
A third of the world’s population is infected with Mycobacterium tuberculosis (MTB) and more than 9 million cases of tuberculosis (TB) are diagnosed annually, resulting in almost 2 million deaths each year (WHO., 2015). TB accounts for more than a quarter of all preventable deaths among adults in TB-endemic countries and a third of deaths among people with HIV infection. These facts make it possible to classify TB as a disease with a high mortality rate in the adult population. The scale of the TB problem is further aggravated by the evolution and global spread of Mycobacterium tuberculosis strains that are resistant to primary and reserve anti-TB drugs. Of particular concern are cases of drug resistance, increasing from multidrug resistance and extensive drug resistance to variants of infection for which no effective therapeutics remain.